Identifying and analyzing low energy availability in athletes: The role of biomarkers and red blood cell turnover - Suzuki, D.; Suzuki, Y. (Nutrients, 2024)
Low energy availability (LEA) is a growing concern that can lead to several problems for athletes. However, adaptation to LEA occurs to maintain balance over time, making diagnosis difficult. In this review, we categorize LEA into two phases: the initial phase leading to adaptation and the phase in which adaptation is achieved and maintained. We review the influence of LEA on sports performance and health and discuss biomarkers for diagnosing LEA in each phase. This review also proposes future research topics for diagnosing LEA, with an emphasis on the recently discovered association between red blood cell turnover and LEA.